Senza mani ! : Provos e biciclette bianche. - Cingolani, Marco; Guarnaccia, Matteo (Milano : Antonio Colombo Arte Contemporanea, 2001)
Aquilanti, Andrea ; Arienti, Stefano ; Arrhenius, Lars ; Avveduti, Sergia ; Prof. Bad Trip ; Bazan, Alessandro ; Benvenuto, Carlo ; Calvert, Mike ; Cannavacciulo, Maurizio ; Capogrosso, Pietro ; Casini, David ; Cingolani, Marco ; Calignano, Pierluigi ; Contin, Andrea ; Damioli, Aldo ; Dellavedova, Mario ; Pasquier, Nathalie Du ; Fusi, Federico ; Galliano, Daniele ; Gilberti, Fausto ; Guarnaccia, Matteo ; Guatta, Giuliano ; Manetas, Miltos ; Pancrazzi, Luca ; Papa, Marco ; Pessoli, Alessandro ; Pontrelli, Gioacchino ; Salvino, Andrea ; Scotto di Luzio, Lorenzo ; Verlato, Nicola ; Vitali, Massimo
Bijlage: Engelse vertaling
Italiaans & Engels
Senza mani ! : Provos e biciclette bianche, Antonio Colombo Arte Contemporanea, Milano, 18.09 12.10.2001
boek